HOW IS ARTIFICIAL INTELLIGENCE CHANGING HR? ADAPTIVE MANAGEMENT FOR THE NEW ENVIRONMENT - Dmytro Antoniuk; Bjoern Sven Ivens; Olexandr Kolyada (Baltic Journal of Economic Studies)
The integration of artificial intelligence (AI) into human resource management (HRM) is a pivotal factor in the transformation of conventional HR practices. The increasing complexity of HR processes, in conjunction with the mounting necessity for personalisation, efficiency and adaptability, underscores the importance of leveraging AI-based solutions within contemporary organisations. The objective of this research is to explore the role of AI in HRM, analyse its impact on adaptive management approaches, and identify key factors that impact the successful implementation of AI in HR processes. The study uses a mixed approach, combining literature review, empirical data collection based on interviews with companies of different sizes, and correlation analysis. The analysis focuses on the adaptability of AI-based HR systems, their impact on employee engagement, productivity and decision-making processes. Special attention is paid to ethical issues such as algorithmic bias and transparency, as well as organisational barriers that may prevent the implementation of AI. The findings of the research demonstrate that the implementation of AI technology has the potential to enhance the efficiency of HR management practices. This enhancement is achieved through the optimisation of recruitment processes, the creation of personalised learning pathways, the facilitation of real-time performance evaluation, and the cultivation of a culture that fosters proactive career development. Adaptive AI-powered HR systems enable organisations to respond expeditiously to market changes, optimise talent management, and minimise operational risks. The study demonstrates that, while SMEs exhibit greater flexibility in implementing AI solutions, large corporations encounter structural and managerial challenges that necessitate strategic adjustments to facilitate effective integration of AI. The practical significance of the study lies in its recommendations for organisations seeking to implement adaptive AI-based HR models. It provides insights on how to optimise the use of AI for talent management, improve HR efficiency and address ethical considerations.